KOMUNIKASI PEMBANGUNAN DALAM PEMBERDAYAAN UMKM DI DESA PELEM KECAMATAN SIMO KABUPATEN BOYOLALI - Safitri, Hany Dwi; Sekar Wangi, Maya; Widiyowati, Estu (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
This research discusses development communication in empowering MSMEs carried out by the Boyolali Regency Cooperatives and Manpower Service using dialogical and top down communication flows by applying a participatory approach in every stage of development, from planning to utilizing the results. This type of research is descriptive research using qualitative methods. The techniques used in this research are in-depth interviews, non-participant observation and documentation. The research results show that development communication in empowering Micro, Small and Medium Enterprises carried out by the Boyolali Regency Cooperatives and Manpower Service applies a participatory approach in every stage of development, from planning to utilizing the results. Some of the main points of implementing this approach are (1) Community participation in the planning stage, namely Micro, Small and Medium Enterprises are involved in discussion forums to convey ideas and the obstacles they face. (2) Community participation in the implementation stage can take various forms, such as labor contributions, provision of materials or moral support that helps facilitate the running of the empowerment program. (3) Community participation in the evaluation stage, namely Micro, Small and Medium Enterprises actors conveying their critical views and assessments regarding the effectiveness and impact of the program implemented by the Boyolali Regency Cooperatives and Manpower Service. (4) Community participation in the results utilization stage, namely Micro, Small and Medium Enterprises actors actively participate by applying the knowledge and skills obtained from the empowerment program, such as strengthening relationships, improving product quality, and utilizing social media for marketing. Keywords: Development Communication, Empowerment of Micro, Small and Medium Enterprises, Approach Participative